Quality Improvement of Nasal Continuous Positive Airway Pressure Therapy in Neonatal Intensive Care Unit - Chien-Yi Chen; An-Kuo Chou; Yu-Lien Chen; Hung-Chieh Chou; Po-Nien Tsao; Wu-Shiun Hsieh (Elsevier, 2017)
Nasal continuous positive airway pressure (NCPAP) therapy is widely used in neonates, but the clinical practice varies. However, nursing practice differs among individuals, and an inappropriate application method may delay the respiratory therapy, influence the beneficial effect of NCPAP, and increase complications. We introduced a quality improvement project to expedite the application of NCPAP therapy and decrease the incidence of nasal trauma. Methods: A new strategy of mobile NCPAP cart with prepacked fixation kits and a written protocol was implemented from April 2006. All medical staff answered a questionnaire to assess their basic knowledge before and after intensive training. The records of the patients who were treated with NCPAP from October 2005 to November 2006 were reviewed. Results: Fifty-nine medical staff were involved in the project, and their mean score for the questionnaire improved from 69.2 points to 98.3 points after training. From October 2005 to November 2006, 113 infants were recruited in total and 82 of them were admitted after the protocol was implemented. The NCPAP cart dramatically shortened the preparation time (from 520 seconds to 72 seconds) and the application time (from 468 seconds to 200 seconds). The use of the nursing protocol significantly decreased the incidence of nasal trauma in the study population (45.2% vs. 19.6%, p = 0.006), but not in infants with a birth weight of < 1000 g. Risk factors for nasal skin trauma included lower gestational age and birth weight, longer duration of NCPAP use, and lack of standardized nursing care. Conclusion: The mobile NCPAP cart with prepacked fixation kits is a practical way of expediting the initiation of NCPAP therapy. The written nursing protocol decreased the incidence of nasal trauma in infants, except for those with an extremely low birth weight.